외국어로서 한국어 교육콘텐츠에서의 성별언어에 대한 인식 - 박덕재(Deok-Jae Park) (한국콘텐츠학회 논문지, 9(8), 2009)
This paper focuses on gender studies with respect to language education for KFL(Korean as a foreign language) students. It also attempts to view the role of gender as exerting influence on language learning and teaching, and surveys KFL teachers' awareness of the role of gender in Korean language education. It is conceivable that teachers who are aware of differences between female and male will be able to take these into account in their teaching; in doing so they will be more effective in their teaching than if they were to teach in ignorance of these differences. The survey for the teachers' awareness of gender difference was conducted through teachers' discussion as the follow-up measure of the questionnaire. A few teachers do not have a clear idea about the importance of gender differences in language teaching, but the majority have cognizance of the matter. For this research, a questionnaire was administered to 71 subjects, consisting 37 intermediate KFL students and 34 advanced KFL students. The result of the questionnaire reveals that 50.4% subjects use their words and intonation without recognizing the gender difference, on the other hand, 49.6% subjects recognize the gender differences in Korean language use. The result should be adopted as a sociolinguistic factor for the contents of second language education. 본 연구는 외국어로서 한국어 연구 중에서 언어와 성의 문제를 분석하기 위하여 교육콘텐츠와 교사-학생의 인식의 관계를 조사하였으며, 또한 외국어 교육에 영향을 미치고 있는 성별언어의 역할을 연구하였다. 성별언어에 대한 교사의 인식과 교육콘텐츠에 대한 균형 있는 시각 및 교사, 학생의 소통은 언어습득의 효과적 결과를 가져올 수 있다. 19명의 교사와 71명의 학습자와의 인터뷰, 설문지 조사를 실시하여 교사는 89.4%가 여성언어가 존재함을 인정하였고, 학생은 49.6%가 성별언어에 대하여 차이점을 인식하고 있었다. 과거보다 언어가 중성화되고 았으며 굳이 남녀 성별언어를 구별하지 않는 이유는 여성의 사회활동 증가에 기언하는 사회적인 영향으로 보고 있었다. 그러므로 문화를 통한 언어교육이 교육콘텐츠의 역할이므로 경우와 시기에 따라 적절하게 이해되어야 할 필요가 있다. 아직 편향된 여성의 지위, 역할, 언어 등이 교재내용에 나타나 있으므로 이는 교사, 학생들의 이해와 수용이 필요하고 교육콘텐츠 개발에 반드시 반영되어야 할 부분이다.